Analisis Campur Kode Pada Tayangan Video Ulasan Makanan Di Konten Tiktok @Farida.Nurhan: Kajian Sosiolinguistik - Amanda Kurnia Dwi Putri; Sophia Rahmawati; Syaiputri, Kenza Abelia; Fanny Arizal; Ade Bayu Saputra (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2026)
This study aims to describe the forms of code-mixing and to identify the factors causing its occurrence in food review videos on the TikTok account @farida.nurhan. A descriptive qualitative approach was applied using qualitative content analysis as its method. Data were collected from eight food review videos uploaded during January–March 2026 through listening and note-taking techniques. Data analysis followed the interactive model of Miles et al. (2014), comprising data reduction, data display, and conclusion drawing. The theoretical framework applied was Suandi’s classification of code-mixing types (in Tyas et al., 2023) and Suwito’s (1985) theory of code-mixing forms. The findings identified 36 instances of code-mixing distributed across three types: outer code mixing (26 data, 72.2%), inner code mixing (8 data, 22.2%), and hybrid code mixing (2 data, 5.6%). The forms of code-mixing found include words, phrases, hybrid words (baster), reduplicated words, idioms, and clauses. The factors contributing to code-mixing include: (1) the speaker’s cultural background, (2) the use of terminology more popular among young audiences, (3) informal and spontaneous speech situations, (4) the speaker’s desire to explain and interpret messages to the audience, and (5) the heterogeneous characteristics of the interlocutors. This study affirms that code-mixing in Farida Nurhan’s speech is not merely an incidental linguistic variation, but rather a reflection of the speaker’s socio-cultural identity and an effective communication strategy for reaching a diverse audience in the digital age.